Women living a discourse of resistance: South African islamist biographies as journeys of everyday political islam - Ahjum, Gadija (Journal of religion in Africa, 2019)
Abstract: For many Muslim South African antiapartheid activists, a renewed understanding of religion in the form of Islamist ideology provided purpose, perseverance, and direction. Becoming part of a collective shaped and informed their public engagement with religion. This paper shows how they used religious discourse to navigate the complexities and ambiguities within their private domains while embarking on an Islamist journey. By suggesting that South African Islamism can best be viewed as the sum of a multitude of journeys of everyday political Islam, this paper argues for an approach that examines a long-term narrative, takes heed of perfectionist ideals, and remains cognizant of everyday realities.